Kualitas Pelayanan, Fasilitas, dan Budaya Kerja Berbasis Digital Governance dalam Meningkatkan Kebahagiaan Masyarakat di Disdukcapil Kota Pariaman - Assyahri, Wahib; Bila, Aziza (Journal of Education on Social Science (JESS), 2024)
The Population and Civil Registration Office of Pariaman City has provided a type of online population document service called Dukcapil Digi Mobile Pariaman. However, this service is less utilized by the community due to the lack of socialization from the Disdukcapil of Pariaman City, and the community does not understand the process of using it, so they prefer manual services. There are also obstacles from the Disdukcapil of Pariaman City it self in improving service quality, namely the lack of facilities and infrastructure such as inadequate service places/rooms and the lack of competent human resources in their fields. This study uses quantitative methods with associative research types that aim to determine the effect of independent variables (service quality, facilities, and digital governance-based work culture) on the dependent variable (community happiness). The sample used in this study was 340 based on the Slovin Formula with a tolerance level of 5%. Sampling using the accidental sampling technique. The data collected from the research results were then processed and analyzed using the simple linear regression formula partially and multiple linear regression simultaneously. The results showed that there was a significant partial influence between service quality on community happiness by 55.5%, facilities on community happiness by 55.4%, and digital governance-based work culture on community happiness by 33.1%. And there is a simultaneous influence of the three independent variables on community happiness of 64.4%. The implications of this research as input and consideration for Disdukcapil Pariaman City in improving their services